1988
DOI: 10.1017/s0022215100106474
|View full text |Cite
|
Sign up to set email alerts
|

Local anaesthetic with vasoconstrictor combinations in septal surgery

Abstract: Local anaesthetic with vasoconstrictor combinations are often used to reduce bleeding and hence improve the operating field in septal surgery. Two commonly used combinations are lignocaine with adrenaline and prilocaine with felypressin (citanest with octapressin). Most surgeons prefer to use lignocaine with adrenaline but because of the risks of cardiac dysrhythmias when used with halothane anaesthetists prefer prilocaine with felypressin. In a trial with lignocaine 2 per cent and adrenaline 1 in 200,000 agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…These agents had been conventionally applied both topically and injected [1]. Infiltration of solutions with adrenaline concentration of 1:100,00-1:200,00 are commonly used while solutions with the concentration of 1:10,000 are commonly used just for topical applications [2,3]. Also infiltration of those agents provide mucoperichondrial flap elevation through hydrodissection in the septal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…These agents had been conventionally applied both topically and injected [1]. Infiltration of solutions with adrenaline concentration of 1:100,00-1:200,00 are commonly used while solutions with the concentration of 1:10,000 are commonly used just for topical applications [2,3]. Also infiltration of those agents provide mucoperichondrial flap elevation through hydrodissection in the septal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Vanniasegaram [11] consider in his prospective study of the use of vasoconstrictors versus saline in septal surgery, that there is no benefits of using adrenaline, without dramatic differences in blood loss and operative time between the two groups. McClymont et al [12] consider the using of local anesthetics with vasoconstrictors an optimal combination for septal surgery. In our opinion, the risk of bleeding is higher in non-tumescent rhinoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Usually Lidocaine is considered as a vasodilator which should actually increase the bleeding in the operative field. Tatjana and colleagues have studied the bleeding in the operative field during septoplasty [7]. He had shown that infiltration of Lidocaine with adrenaline has reduced the bleeding proving better visibility of surgical field.…”
Section: Pain Scorementioning
confidence: 99%
“…We should remember that Lidocaine is not just a placebo but a drug that can cause toxicity at higher doses [5]. Role of infiltrating various local anesthetic agents in surgeries like tonsillectomy, nasal surgery [6][7][8], tooth extraction [9] etc. were studied before.…”
Section: Introductionmentioning
confidence: 99%